2019
DOI: 10.3389/fenrg.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene-Based and Amine-Linked Nanoporous Networks for Efficient CO2 Capture and Separation

Abstract: A set of five nanoporous (pore size <100 nm) amine-functionalized and triptycene-based organic polymers (TBPALs) were prepared using commercially available phenols (such as quinol and phloroglucinol) and triptycene amines. C-N bonds were formed in the polymerization reactions without employing transitional metal catalysts such as Pd II or CuI. TBPALs demonstrated their ability to reversibly capture small gas molecules such as CO 2 , H 2 , CH 4 , and H 2. Highest uptake of CO 2 and H 2 was observed for TBPAL2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Thus, a variety of triptycene POPs linked via amines 71,72 or phenazines 73 have been employed to endow the polymers with suitable functional active sites. Both amines and phenazines provide basic sites which help polarizing CO 2 , thus enabling for example the cycloaddition of epoxides to carbonates.…”
Section: Pops For Co2 Capture and Separationmentioning
confidence: 99%
“…Thus, a variety of triptycene POPs linked via amines 71,72 or phenazines 73 have been employed to endow the polymers with suitable functional active sites. Both amines and phenazines provide basic sites which help polarizing CO 2 , thus enabling for example the cycloaddition of epoxides to carbonates.…”
Section: Pops For Co2 Capture and Separationmentioning
confidence: 99%
“…38 The presence of micropores and the associated high surface areas are attributed to the three-dimensional and contorted structure of triptycene motifs present in the polymeric backbone. [38][39][40] Triptycene-based microporous organic polymers are also reported to demonstrate interesting applications in materials chemistry, such as small gas molecules (CO 2 , H 2 , CH 4 and N 2 ) capture and separation (CO 2 /CH 4 , CO 2 /N 2 and CH 4 /N 2 ), [41][42][43][44][45] toxic dye removal and iodine adsorption for environmental remediation. [46][47][48][49][50][51] Thus it is expected that the material incorporating triptycene and octa-functional OVS would yield a highly porous network.…”
Section: Introductionmentioning
confidence: 99%
“…In recent literature related to POPs derived from triptycene-based monomers, it has been observed that such materials have reasonable surface areas with inherent hierarchical porosity for applications such as CO 2 capture and hydrogen storage. ,, This prompted us to investigate the Brunauer–Emmett–Teller (BET) surface areas and the pore size distributions of TBOSBL s. Thus, to determine the porous properties of TBOSBL s in detail, N 2 adsorption–desorption isotherms were recorded. The features of N 2 sorption isotherms (collected at 77 K, Figure A) of TBOSBL s suggest that they may be classified as type-II isotherms .…”
Section: Results and Discussionmentioning
confidence: 99%